Gut-lung axis in allergic asthma: microbiota-driven immune dysregulation and therapeutic strategies - Lv, Jian; Zhang, Yu; Liu, Shuang; Wang, Ruoyu; Zhao, Jianan (Frontiers in Pharmacology, 2025)
BackgroundAllergic asthma, a chronic respiratory disorder, is intricately linked to gut microbiota dysbiosis and metabolite perturbations through the gut-lung axis.ObjectiveThis review the relationship between microbial immune crosstalk and the onset of asthma, with the aim of determining the mechanism by which gut microbiota drives the onset of asthma and providing evidence for therapeutic interventions.MethodsLiterature search was conducted on PubMed using keywords (“gut microbiota” or “gut microbiota” or “gut microbiota metabolites” or “lung gut axis”), (“allergic asthma” or “asthma”), and (“immune regulation”), without date restrictions. Including peer-reviewed studies on human/animal models, articles that do not meet the requirements are excluded.ResultMicrobial imbalance in asthma patients—marked by reduced α-diversity, depletion of immunomodulatory taxa (e.g., Bifidobacterium, Faecalibacterium), and enrichment of pathobionts—disrupts short-chain fatty acid (SCFA) and tryptophan metabolism, skewing Th17/Treg balance toward Th2-dominated inflammation and airway hyperresponsiveness. SCFAs, particularly butyrate, activate GPR41/43 receptors and inhibit histone deacetylases (HDACs), enhancing Treg differentiation while suppressing Th2/Th17 responses. Tryptophan metabolites, such as indole derivatives, alleviate pulmonary inflammation via aryl hydrocarbon receptor (AhR)-dependent IL-22 production. Clinically, diminished SCFA levels correlate with impaired immune tolerance and airway remodeling, while probiotics (Lactobacillus, Bifidobacterium), prebiotics, and high-fiber diets restore microbial equilibrium, attenuating asthma severity.ConclusionFuture research must integrate multi-omics data to delineate strain-specific functions, host-microbe interactions, and individualized responses influenced by genetics, diet, and environmental factors. This review underscores the gut microbiota’s dual role as a biomarker and therapeutic target, advocating for microbiota-directed strategies in asthma prevention and precision medicine.